2017
DOI: 10.1002/anie.201709261
|View full text |Cite
|
Sign up to set email alerts
|

CODH‐IV: A High‐Efficiency CO‐Scavenging CO Dehydrogenase with Resistance to O2

Abstract: CO dehydrogenases (CODHs) catalyse the reversible conversion between CO and CO . Genomic analysis indicated that the metabolic functions of CODHs vary. The genome of Carboxydothermus hydrogenoformans encodes five CODHs (CODH-I-V), of which CODH-IV is found in a gene cluster near a peroxide-reducing enzyme. Our kinetic and crystallographic experiments reveal that CODH-IV differs from other CODHs in several characteristic properties: it has a very high affinity for CO, oxidizes CO at diffusion-limited rate over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 26 publications
6
84
0
1
Order By: Relevance
“…In the case of CODH 1, the current even slowly increases further during the minute that follows the injection, reflecting an increase in activity, probably an activation by CO. After the plateau, the current decreases in a sigmoidal fashion, ending in a perfect mono-exponential decay. This is exactly as observed in the case of other CODHs [15,23]. CODHs are in general so active for CO oxidation that the electrode rotation cannot prevent depletion of CO in the vicinity of the electrode: therefore, mass-transport limitations have to be taken into account.…”
Section: Dependence Of Activity On Potential and Catalytic Biassupporting
confidence: 67%
See 3 more Smart Citations
“…In the case of CODH 1, the current even slowly increases further during the minute that follows the injection, reflecting an increase in activity, probably an activation by CO. After the plateau, the current decreases in a sigmoidal fashion, ending in a perfect mono-exponential decay. This is exactly as observed in the case of other CODHs [15,23]. CODHs are in general so active for CO oxidation that the electrode rotation cannot prevent depletion of CO in the vicinity of the electrode: therefore, mass-transport limitations have to be taken into account.…”
Section: Dependence Of Activity On Potential and Catalytic Biassupporting
confidence: 67%
“…Recently, we suggested that a tight packing of residues at the backside of the [3Fe-4S]subcluster of the C cluster can contribute to O 2 -resistance in Ch CODH IV, whereas the loose packing is typical of highly O 2 -sensitive CODHs [15]. Residues M556, F322, I206, C304, K559 and S557 of CooS2 are in close contact to the backside of the C cluster ( figure 3B), resembling more the tightly shielded backside of Ch CODH IV than the loosely packed Ch CODH II.…”
Section: Active Sitementioning
confidence: 99%
See 2 more Smart Citations
“…The heterologous production in E. coli of Ch CODH-II or -IV, for instance, leads to the formation of nickel-loaded, mature and active CODH [8, 46, 47]. It is important to note that in these studies E. coli is grown in the presence of high concentrations of nickel (more than 0.5 mM) to favor nickel insertion into CODH.…”
Section: Cooc-dependent Maturationmentioning
confidence: 99%